PKMBP ECOCR (ECOTOURISM CENTER OF CINTA RAJA) UNTUK MENGEMBANGKAN POTENSI DESA WISATA MELALUI DIGITALISASI DESA DI DESA CINTA RAJA KECAMATAN LANGSA TIMUR MENUJU PARIWISATA 4.0 - Yani Rizal; Kiagus Muhammad Zain Basriwijaya; Siti Balqies Indara; Fairus Fairus (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
Cinta Raja Village is a village that has a lot of natural potential, so that in July 2021 the Langsa City Government set Cinta Raja Village to be a tourist village under the Tunas Muda BUMG. One of the destinations or potential tourist villages in Cinta Raja Village is mangrove forest exploration, traditional Acehnese culinary tourism, monitoring of migratory birds, and tika seukèe (Pandan leaf woven mat). BUMG Tunas Muda is still a beginner and still young in developing a tourism village business, but partner members are quite skilled in managing the tourism potential in the Cinta Raja village, there are two priority problems faced, namely problems in promoting or marketing EcoCR (Ecotourism Center of Cinta Raja) ), the number of tourists is not maximized because the marketing or promotions that have been carried out so far are not comprehensive, marketing is only done by word of mouth so that the number of tourists who come is not optimal due to the lack of information obtained by tourists about the potential of Cinta Raja Village; and Partners do not yet have a financial accounting system that is well structured and recorded in a disciplined and orderly manner. Overcoming these problems the solutions are making village websites, BUMDes websites, selling tour package websites, making EcoCR (Ecotourism Center of Cinta Raja) logos, socializing website utilization, website management training, and assisting in making cash flow bookkeeping or simple financial reports by handling existing problems. increase Enhancement of partner empowerment.